Tcl and the Tk Toolkit. - Ousterhout, John K., ....-; Jones, Ken, ....- (Upper Saddle River : Addison-Wesley, 2010)
The world's #1 Tcl/Tk tutorial, now thoroughly updated for the brand-new Tcl 8.5, written by the creator of Tcl--Perfect for newcomers who want to master Tcl/Tk 8.5 fast - and experienced Tcl/Tk programmers who want to master its advanced features.-Includes unsurpassed coverage of Tcl 8.5's updated C programming interface.-Straightforward, concise, and packed with reliable code examples.Tcl and the Tk Toolkit, Second Edition is the fastest way for newcomers to master Tcl/Tk. And it's also the most authoritative resource for experienced Tcl/Tk programmers who want to master Tcl's important C interfaces, both to integrate Tcl/Tk code with C applications, or to create new Tcl/Tk commands. Co-authored by Tcl/Tk creator John Osterhout, it shares the extraordinarily clarity and careful organization that made the First Edition a worldwide Tcl/Tk best-seller, while incorporating substantial updates for the brand-new Tcl/Tk 8.5. For newcomers, it offers a lucid introduction to the language and its key features, as well as practical, hands-on guidance for developing production applications. For experienced Tcl/Tk programmers, it presents unsurpassed coverage of Tcl/Tk's C interfaces, with examples of using C to create new Tcl commands, and integrating Tcl with existing C applications. (A bonus section on using Tcl/Tk interfaces to develop custom Tk widgets is available for download.)